Excess Ultraviolet Emission at High Galactic Latitudes: A New Horizons View - Jayant Murthy; J. Michael Shull; Marc Postman; Joel Wm. Parker; Seth Redfield; Nathaniel Cunningham; G. Randall Gladstone; Jon P. Pineau; Pontus Brandt; Anne J. Verbiscer; Kelsi N. Singer; Harold A. Weaver; et al. (The Astronomical Journal)
We present new observations of the cosmic ultraviolet background (CUVB) at high Galactic latitudes (∣ b ∣ > 40 ^∘ ), made using the Alice UV spectrograph on board the New Horizons spacecraft. These observations were taken at about 57 au from the Sun, outside much of the foreground emission affecting previous missions, and allowed a new determination of the spectrum of the CUVB between 912–1100 Å and 1400–1800 Å. We found a linear correlation between the CUVB and the Planck E ( B − V ) with offsets at zero-reddening of 221 ± 11 photon units at 1000 Å and 264 ± 24 photon units at 1500 Å (4.4 ± 0.2 nW m ^−2 sr ^−1 at 1000 Å and 5.3 ± 0.5 nW m ^−2 sr ^−1 at 1500 Å). The former is the first firm detection of the offset in the range 912–1100 Å while the latter result confirms previous results from the Galaxy Evolution Explorer, showing that there is little emission from the solar system from 1400 to 1800 Å. About half of the offset may be explained by known sources (the integrated light of unresolved galaxies, unresolved stars, emission from ionized gas, and two-photon emission from warm hydrogen in the halo) with the source of the remaining emission as yet unidentified. There is no detectable emission below the Lyman limit with an upper limit of 3.2 ± 3.0 photon units.